Protective effect of green tea extract on the deltamethrin-induced toxicity in mice testis: An experimental study - Hoda Bagherpour; Abbasali Karimpour Malekshah; Fereshteh Talebpour Amiri; Mohammad Azadbakht (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background Deltamethrin (DM) is one of the environmental factors that can have destructive effects on the male fertility. Green tea (GT) as a medicinal herb, has antioxidant property. Objective The present study investigated the protective role of GT extract in improving the harmful effects of DM on the testis. Materials and Methods In this experimental study, 35 adult male mice (25-30 gr) were divided in to five groups (n = 7/each). The control group received only normal saline. Sham received 0.2 ml corn oil. Green tea group received only GT of 150 mg/kg. bw; deltamethrin group received the DM at a dose of 0.6 mg/kg. bw; GT + DM received both GT and DM. The effect of GT was assessed by measuring oxidative stress markers, sperm parameters, histological and immunohistochemical analysis. Results The results showed that the count and motility of spermatozoa, testosterone, and Malondialdehyde significantly decreased (p < 0.001) and the abnormal spermatozoa increased (p < 0.001) in DM group compared to control group. Moreover, enhanced caspase-3expression and apoptosis were observed in DM-treated mice compared to control group. Histologically, DM with a degenerative effect on testicular tissue reduced the spermatogenesis progenitor cells. The epithelial height and the diameter of the seminiferous tubules were also reduced in the DM group. Treatment with GT in the DM-treated mice significantly improved these changes. Conclusion With these findings, it was concluded that the GT treatment with antioxidant activity and anti-apoptotic property could protect the testicular injury induced by DM.